Ni-Catalyzed Regioselective Alkylarylation of Vinylarenes via C(sp3)–C(sp3)/C(sp3)–C(sp2) Bond Formation and Mechanistic Studies - KC, Shekhar; Dhungana, Roshan K; Shrestha, Bijay; Thapa, Surendra; Khanal, Namrata; Basnet, Prakash; Lebrun, Robert W; Giri, Ramesh (Journal of the American Chemical Society, 2018)
We report a Ni-catalyzed regioselective alkylarylation of vinylarenes with alkyl halides and arylzinc reagents to generate 1,1-diarylalkanes. The reaction proceeds well with primary, secondary and tertiary alkyl halides, and electronically diverse arylzinc reagents. Mechanistic investigations by radical probes, competition studies and quantitative kinetics reveal that the current reaction proceeds via a Ni(0)/Ni(I)/Ni(II) catalytic cycle by a rate-limiting direct halogen atom abstraction via single electron transfer to alkyl halides by a Ni(0)-catalyst.